Cointegration and causality between non-bank financial intermediaries and economic growth in Malaysia: an ARDL bounds testing approach - Islam, Mohd Aminul; Zakaullah, Muhamad Arif (2009)
This paper aims to investigate the causal relationship between nonbank financial intermediaries (NBFIs) and per capita economic growth in Malaysia for the period 1974-2004. The study employs the ARDL bounds testing approach to cointegration. The Granger non causality test in a multivariate vector error correction mechanism (VECM) framework is carried out to ascertain the direction of causality among the variables. The test result suggests that nonbank financial intermediaries and economic growth are cointegrated when economic growth is the dependent variable but are not cointegrated when the other variables are treated as the dependent variables. The result shows evidence of a long-run causality running from nonbank financial intermediaries to per capita economic growth, but not vice versa.